KASUS PERNIKAHAN DINI: DALAM KOMPILASI HUKUM ISLAM - Dini Permana Sari (Universitas Islam Depok, 2021)
Marriage in Islam is a suggestion for the benefit of Muslims as a whole. The ideological reason is that early marriage will increase the number of offspring, increasing the Muslim population. Analysis of Early Marriage Cases in Various Perspectives From UNICEF's data on early marriage and the examples of cases of early marriage in Indonesia, which have been mentioned previously, shows the dynamics of knowledge about marriage in society, especially in Indonesia. The validity of marriage in Islam is regulated in the pillars of marriage and its conditions, which have been included in the Compilation of Islamic Law. Concept of Marriage in Islam 1. Concept of Early Marriage Early marriage means the union or bonding of a man and a woman at an early age. Case Study of Early Marriage 1. Before conducting a legal analysis of the case, it is necessary to understand the meaning of early marriage, the age limit in a positive legal and psychological perspective.